A Bibliography of Articles Published in Bodhi: An Interdisciplinary Journal - Dhungana, Smriti (Bodhi: An Interdisciplinary Journal, 2024)
This article is a bibliograpic review, analysis, interpretation and discussion of Bodhi: An Interdisciplinary Journal, published by Kathmandu University (KU) from 2007 to 2023. During its 16-year journey, Bodhi, over nine issues, published 119 articles by scholars and researchers from various disciplines, particularly Humanities and Social Sciences.